FORMULASI SEDIAAN SABUN PADAT TRANSPARAN DARI EKSTRAK ETANOL DAUN KEMBANG BULAN (TITHONIA DIVERSIFOLIA) SEBAGAI SABUN WAJAH - Dwi Mulyani; Deva Himer Harsep Rosi; Hilmarni Hilmarni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The phytochemical test of the ethanol extract of Kembang Bulan leaves showed that it contained flavonoids, alkaloids and tannins. The extract against Staphylococcus aureus has an inhibitory diameter of 12mm with an MIC of 6.25 mg/mL. Kembang Bulan Leaf Extract Gel (Tithonia diversifolia) significantly accelerates the healing of burns in male Sparaque-Dawley white rats. This study aims to determine whether the ethanol extract of Kembang Bulan leaves (Tithonia diversifolia) can be formulated as transparent solid soap as facial soap with a concentration of 1% , 2%, and 3%, using the hot process method. The results of the study proved that the ethanol extract of Kembang Bulan leaves can be formulated as a transparent solid facial soap that meets the evaluation standards for organoleptic tests, water content tests, pH tests, irritation tests and foam stability tests.